Technical Guidance 21st Century Learning Application to Improve the Pedagogic and Professional Competence of Elementary School Teacher - Dyoty Auliya Vilda Ghasya; Kartono Kartono (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Abstract At this time the 21st century is known by all audiences as the era of knowledge which is used as a foundation in various aspects of the wheel of life with the characteristic of providing information anywhere and anytime and increasing the interaction of world citizens either directly or indirectly. Talking about 21st century skills, education today should not only be about knowledge of the subjects being taught but also lead to leadership, responsibility, problem solving, analytical thinking, adaptability, communication, initiative, self-direction, creativity, cross-cultural skills, and work. same. Through this PKM activity bridges teachers to have 21st century skills in the form of (1) Critical Thinking Skills; (2) Ability to Solve Problems; (3) Communication and Collaboration; (4) Creativity and Innovation; (5) Information, Communication, and Technology Media Literacy. Teachers as people who daily wrestle with the world of education and have direct contact with students in schools must be able to change their teaching style according to the needs of the 21st century.